Exploring the association between tissue sodium content, heart failure subtypes, and symptom burden: insights from magnetic resonance imaging - Djawid Hashemi; Djawid Hashemi; Djawid Hashemi; Djawid Hashemi; Karl Jakob Weiß; Karl Jakob Weiß; Karl Jakob Weiß; Patrick Doeblin; Patrick Doeblin; Patrick Doeblin; Moritz Blum; Radu Tanacli; et al. (Frontiers in Cardiovascular Medicine)
AimsHeart failure (HF) is a complex clinical syndrome with high morbidity and mortality, influenced significantly by sodium balance. Recently, magnetic resonance imaging (MRI) has emerged as a non-invasive method to evaluate tissue sodium load in HF patients. This proof-of-principle study investigates the association between tissue sodium content, assessed by MRI, and HF-related baseline parameters in an outpatient cohort of patients with chronic heart failure, including those with reduced ejection fraction (HFrEF), mildly reduced ejection fraction (HFmrEF), and preserved ejection fraction (HFpEF).Methods and resultsThis prospective study included 29 HF patients (10 HFpEF, 12 HFmrEF, and 7 HFrEF) recruited from two centers in Berlin, Germany. Patients underwent MRI to assess tissue sodium content in the lower extremity. Tissue sodium content was analyzed in relation to baseline HF parameters, including renal function, natriuretic peptide levels, clinical signs of congestion, diuretic use, and New York Heart Association (NYHA) functional class. No significant differences in tissue sodium content were observed between the three HF entities. Sodium values did not differ significantly with clinical signs of congestion or diuretic use. No significant correlations were found between tissue sodium content and renal function (eGFR) or natriuretic peptide levels (NT-proBNP) in any HF group overall. However, explorative analyses showed a positive correlation between free (r = 0.79, p = 0.036) and total (r = 0.79, p = 0.036) tissue sodium content in the skin and NT-proBNP levels in HFrEF patients, but not in HFmrEF and HFpEF. Similarly, there was a correlation between kidney function and both free (r = −0.64, p = 0.025) and total (r = −0.61, p = 0.035) skin sodium in patients with edema and no prior use of loop diuretics, but no correlation for kidney function and both free and total skin sodium in symptomatic patients with established diuretic therapy or asymptomatic patients with no diuretic therapy.ConclusionOur findings provide exploratory insights into the potential diagnostic value of tissue sodium content in HF, particularly in HFrEF patients. With findings showing an association of tissue sodium content with NT-proBNP levels in HFrEF patients and with kidney function in edema patients without prior loop diuretic use, further research is needed to understand the role of tissue sodium content in HF pathophysiology and its potential diagnostic and prognostic implications. Trial registrationGerman Clinical Trials Register (DRKS), registration number (DRKS00015615).